2016
DOI: 10.1007/s11897-016-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Analysis in Heart Failure

Abstract: Heart failure (HF) is a clinical condition that presents high morbidity and mortality and is one of the main reasons for hospital admissions all over the world. Although biochemical processes that occur in the body during heart failure are known, this syndrome is still associated to poor prognosis. Exhaled breath analysis has emerged as a promising noninvasive tool in different clinical conditions and, recently, it has been also tested in patients with HF. This review presents the main breath HF biomarkers, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Arterial ketone body ratio, which reflects hepatic mitochondrial oxidation-reduction potential, is independently associated with cardiac death in patients with acute heart failure [21]. Breath acetone level, which reflects blood ketone bodies, has been reported to be a prognostic factor in heart failure patients with reduced ejection fraction [22], [23]. In patients with hemodialysis, circulating ketone bodies predict cardiovascular events [24].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial ketone body ratio, which reflects hepatic mitochondrial oxidation-reduction potential, is independently associated with cardiac death in patients with acute heart failure [21]. Breath acetone level, which reflects blood ketone bodies, has been reported to be a prognostic factor in heart failure patients with reduced ejection fraction [22], [23]. In patients with hemodialysis, circulating ketone bodies predict cardiovascular events [24].…”
Section: Discussionmentioning
confidence: 99%
“…socio-demographic, clinical examination, medical condition, lab tests, medication intake, phenotypic data, sensor data) along with machine learning techniques are presented in [24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]49]. Recent studies have identified certain biomarkers which strongly correlate with the HF severity, progression and mortality [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81], while the progress in analytical chemistry and biosensor development allowed their detection in saliva and breath [82][83][84][85] with prominent merits due to the easy and non-invasive sample collection. The Event prediction module aims to inform the experts about the possible presence of adverse events (relapses and mortality): (i) by introducing saliva and breath biomarkers into the adverse event prediction process, (ii) based on a machine le...…”
Section: Event Prediction Modulementioning
confidence: 99%
“…Stress resulting from a disturbance in the balance of reactive oxygen species (ROS) and antioxidant defence induces myocyte hypertrophy, cell apoptosis and calcium overload associated with oxidation of membrane phospholipids, proteins and DNA 4 5. Accurate measurement of oxidative stress in vivo is challenging, but analysis of exhaled breath analysis has emerged as a non-invasive tool, and it has been evaluated in patients with CHF 6. Measurement of exhaled acetone, a volatile component of ketone bodies produced by decarboxylation of acetoacetate, was found to be a useful non-invasive method of evaluating congestive haemodynamics in patients with non-ischaemic CHF 7…”
Section: Introductionmentioning
confidence: 99%